Improving Student Participation in Learning Through Discovery Learning Methods in Social Studies Learning - Rahmania Rahman (Peneliti.net, 2022)
The purpose of this study was to determine whether using the Discovery Method could increase student participation in social studies subjects at SMP Negeri 2 Tondano. Data collection techniques using data collection techniques consisting of interviews and also observation. Data collected from interviews and observations on student activities and also educator activities. The use of the Discovery method to increase student participation in SMP Negeri 2 Tondano is marked by an increase in the percentage of both students answering questions, completing assignments and tests and taking notes.